Position Control of IT-Robot manipulator using Multi–Loop FOPID - Mohammed, Reham H. (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2019)
Position control of the manipulator has been noted for its difficulty as the result of the so-called dynamic stability problem, parameter uncertainty and dynamic coupling. This work focused on position control of the first four degree of freedom (DOF) of IT-Robot manipulator using Fractional Order PID (FOPID) controller that can conquer this difficulty. All procedure description to model of the manipulator and control has been detailed and simulated using MATLAB R2015a/Simulink; from the mechanical model generation in SimMechanic where, the manipulator joint is moved using DC motor. Parameters of FOPID controller are optimized using GA. The controller effectiveness is analyzed for set point tracking. By simulation results, it was observed that FOPID controller give better response with minimum error than PID controller for the position control of the IT-robot manipulator.